2006
DOI: 10.1509/jppm.25.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Heightening Adolescent Vigilance toward Alcohol Advertising to Forestall Alcohol Use

Abstract: The authors structured an antialcohol intervention program for adolescents to help them develop negative attitudes toward alcohol advertising, to develop strategies for coping with the techniques used in alcohol advertisements, and to reduce their intentions to drink in the future. The authors derived the program from theories of inoculation, reactance, associative learning, and persuasion knowledge. Young adolescents who experienced the intervention—in particular, those who had drunk alcohol—reported greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Research conducted in the context of alcohol advertising has shown some success in increasing such vigilance, even among the usually skeptical teenage audience (Goldberg et al, 2006). In one study, sixth-grade students participated in five 50-minute lessons on alcohol advertisers' persuasive tactics and how to cope with them (Goldberg et al, 2006).…”
Section: Effect Of Warning Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted in the context of alcohol advertising has shown some success in increasing such vigilance, even among the usually skeptical teenage audience (Goldberg et al, 2006). In one study, sixth-grade students participated in five 50-minute lessons on alcohol advertisers' persuasive tactics and how to cope with them (Goldberg et al, 2006).…”
Section: Effect Of Warning Messagesmentioning
confidence: 99%
“…Research conducted in the context of alcohol advertising has shown some success in increasing such vigilance, even among the usually skeptical teenage audience (Goldberg et al, 2006). In one study, sixth-grade students participated in five 50-minute lessons on alcohol advertisers' persuasive tactics and how to cope with them (Goldberg et al, 2006). Compared with a control group that did not receive this training, those students who had received the training demonstrated greater persuasion knowledge and coping behavior, and they were more negative toward alcohol advertisers.…”
Section: Effect Of Warning Messagesmentioning
confidence: 99%
“…Public policy marketers have used teen interventions to develop skills for resistance to alcohol advertising (Goldberg et al 2006) and to resist group pressure for drug and alcohol consumption (Rose, Bearden, and Teal 1992). Recent approaches outside marketing have used school and community interventions targeting parents in addition to teens.…”
Section: General Discussion and Future Researchmentioning
confidence: 99%
“…Social marketing strategies to reduce teen drinking (counter marketing) have included reducing negative peer influence, changing normative beliefs and/or motivation to comply, and self-presentation or self-image strategies, via advertising or intervention (Kelly, Slater, and Karan 2002;Rose, Bearden, and Teel 2001), and developing advertising persuasion coping behaviors (Goldberg et al 2006). Verplanken and Wood (2006) elaborate on a number of ''downstream'' and ''upstream'' interventions to prevent the development of, or reduce, detrimental habits such as drinking.…”
Section: Alcohol and Family Policy In North Americamentioning
confidence: 99%
“…In these cases, Stiff and Mongeau (2003) argue that it is only necessary to provide a counter argument for inoculation to work. This has been the case when inoculation has been used with teenagers to help form resistance to alcohol and tobacco use (Pfau, Van Bockern, & Kang, 1992;Goldberg, Niedermeier, Bechtel, & Gorn, 2006).…”
Section: Inoculation Against Persuasionmentioning
confidence: 99%